Effectiveness of Progressive Muscle Relaxation Compared to BL 23 and GV 3 Point Acupressure Therapy on Reducing Back Pain Intensity in Third Trimester Pregnant Women - Pawestri, Pawestri; Yunitasari, Esti; Khayati, Nikmatul; Pranata, Satriya (Scripta Medica, 2024)
Background/Aim: Back pain is one of the most common discomforts experienced by pregnant women in the third trimester of pregnancy. Interventions that can be done to overcome this are progressive muscle relaxation or acupressure at the BL 23 and GV 3 points. The aim was to determine the effectiveness of progressive muscle relaxation with BL 23 and GV 3 acupressure to reduce low back pain in third trimester pregnant women.Methods: Quasi-experimental research design method with a two-group pretest and post-test design approach was conducted. The total sample was 88 with inclusion criteria - third trimester pregnant women who experienced back pain. Pain was measured with numerical rating scale (NRS) and analysed using Wilcoxon test. Results: The average reduction in back pain for pregnant women after progressive muscle relaxation was 2.12, while the average reduction in back pain for pregnant women after BL 23 and GV 3 acupressure was 1.50. There is a mean difference between the two (0.62), so it can be concluded that there was a difference in the effectiveness of reducing back pain for pregnant women in the third trimester between the progressive muscle relaxation intervention and the respondents' pain scale after the acupressure therapy intervention at points BL 23 and GV 3.  Conclusion: Back pain for pregnant women in the third trimester can be treated with progressive muscle relaxation therapy or acupressure at points BL 23 and GV 3 to reduce back pain. Progressive muscle relaxation therapy was more effective. Progressive muscle relaxation can be done by pregnant women themselves when back pain occurs.
Keywords: Back pain; Pregnant women; Progressive muscle relaxation; BL 23; GV 3; Acupressure